2019
DOI: 10.12911/22998993/113189
|View full text |Cite
|
Sign up to set email alerts
|

Phytotoxicity of Contaminated Sand Containing Crude Oil Sludge on Ludwigia octovalvis

Abstract: This present research work was conducted to determine the phytotoxic effects on tropical native plants, Ludwigia octovalvis, in order to assess its application for phytoremediation of crude oil sludge in contaminated sand. For this purpose of study, L. octavalvis plants were planted in containers containing different proportion of spiked real crude oil sludge in sand (10%, 50%, and 100% (v/v)). Degradation of crude oil sludge by L. octovalvis was measured in terms of total petroleum hydrocarbons (TPH) and was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Various authors have reported that PR is a non-destructive technology in wetland that requires a long time to decontaminate soil, depending on the concentration of crude oil (Marcek et al 2000;Lee et al 2015;Shehzadi et al 2015;Policarpo et al 2020). Different wetland plants have shown to be able to remove TPH from soil: Scirpus grossus removed 66.6% of TPH in soil contaminated with 0.25% diesel-water; Typha domingensis, Phragmites australis, Leptochloa fusca, and Brachiaria mutica removed 99.13% of hydrocarbons in wetland soil contaminated with 319 mg/L of petroleum at month 18 (Almansoory et al 2017;Alanbary et al 2019). These authors argue that the use of PR in contaminated wetlands stabilizes the petroleum through the in uence of the abundant root systems, retaining and enveloping hydrocarbons, which in turn favors the establishment of microorganisms with CO metabolic capacity that can use carbon of biogenic and crude oil (Atlas and Bartha 2002;Cai et al 2010;Rivera-Cruz et al 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various authors have reported that PR is a non-destructive technology in wetland that requires a long time to decontaminate soil, depending on the concentration of crude oil (Marcek et al 2000;Lee et al 2015;Shehzadi et al 2015;Policarpo et al 2020). Different wetland plants have shown to be able to remove TPH from soil: Scirpus grossus removed 66.6% of TPH in soil contaminated with 0.25% diesel-water; Typha domingensis, Phragmites australis, Leptochloa fusca, and Brachiaria mutica removed 99.13% of hydrocarbons in wetland soil contaminated with 319 mg/L of petroleum at month 18 (Almansoory et al 2017;Alanbary et al 2019). These authors argue that the use of PR in contaminated wetlands stabilizes the petroleum through the in uence of the abundant root systems, retaining and enveloping hydrocarbons, which in turn favors the establishment of microorganisms with CO metabolic capacity that can use carbon of biogenic and crude oil (Atlas and Bartha 2002;Cai et al 2010;Rivera-Cruz et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The biological balance of oil-contaminated soil changes according to the living organisms that inhabit it. Soil contamination with hydrocarbons can even have a positive effect on the biology of the organisms that inhabit historically contaminated environments (González-Moscoso et al 2017;Orocio-Carrillo et al 2019;Alanbary et al 2019;Rodríguez-Uribe et al 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Water samples of 100 mL each from growth medium were taken regularly in clean bottle from each aquarium on tasting time for all phytotreatment to analyse diesel as total petroleum hydrocarbon (TPH). Liquid-liquid extraction method, and gas chromatography were used to determine TPH concentration in the water [16] according to procedure by the Environmental Protection Agency, EPA Method 8041 [17]. Dichloromethane (Merch, Germany) was utilized as a solvent.…”
Section: Tph Detection In Watermentioning
confidence: 99%
“…At high concentrations, H 2 O 2 induces programmed cell death (Dat et al 2000), also called apoptosis. Cell death can occur as a result of the role played by H 2 O 2 in physicochemical reactions that convert high-molecular-weight acids into lipid peroxide and degrade cell wall proteins and nucleic acids (Alanbary et al 2019;Odukoya et al 2019;Sachdev et al 2021). Plant resistance to abiotic stress manifests in its foliage and root morphology, as well as in cell metabolism, including synthesis of H 2 O 2 and antioxidant molecules (Soares et al 2012;Siqueira-Soores et al 2013).…”
Section: Introductionmentioning
confidence: 99%